Effect of Fermentation Time and Starbio Bioactivator Type and Local Microorganism (MOL) “Ginta” on The Nutritional Quality of Cassava Tuber Skin (Manihot Utilisima) - Bahria Nasution; Hasnudi .; Nurzainah Ginting; Yunilas .; Hamdan . (Universitas Sumatera Utara, 2018)
Abstract. BAHRIA NASUTION, 2018.